Turritella terebraShell Synthesized Calcium Oxide Catalyst for Biodiesel Productionfrom Chicken Fat - Sinin, Hamdan; Abu Saleh, Ahmed; Reddy, Amarnadh N.R.; Mohd Nurfirdaus, Mohiddin (Trans Tech Publications, Switzerland, 2020)
Heterogeneous catalyst has been viewed as a promising catalyst for biodiesel production. This study employed Turritella terebra (TT) shell as a source for synthesizing heterogeneous CaO catalyst for biodiesel production via transesterification by utilizing chicken fat as a feedstock. The TT shell CaO catalyst was characterized and its catalytic performance was studied. The spectrographic methods that include FTIR, SEM, PSA, and BET-BJH were employed for characterization of the synthesized CaO. The TT shell CaO catalyst optimally produced chicken fat biodiesel (CFB) with reaction parameters at catalyst concentration of 4 wt%, chicken fat to methanol molar ratio of 1:12, reaction temperature of 60°C, and reaction time of 90 min. The optimal yield was 94.03% and the TT shell CaO catalyst still yield 79.19% of CFB on the fifth cycle of reaction. This study has implied that TT shell is a feasible and attractive renewable source of heterogeneous CaO catalyst for biodiesel production.